The Utility of PRAME and Ki-67 as Prognostic Markers for Cutaneous Melanoma - Asato, Marcel Arakaki [UNESP]; Neto, Francisco Alves Moraes; Moraes, Marcelo Padovani de Toledo [UNESP]; Ocanha-Xavier, Juliana Polizel [UNESP]; Takita, Luiz Carlos; Fung, Maxwell A.; Marques, Mariangela Esther Alencar [UNESP]; Xavier, José Cândido Caldeira [UNESP] (Wolters Kluwer, 2025)
Cutaneous melanoma can lead to metastasis, and it is associated with high mortality. Currently, there are no widely accepted immunohistochemistry markers for melanoma prognosis in routine staging. Preferentially expressed antigen in melanoma (PRAME) is a possible biomarker for prognosis in several non-cutaneous neoplasms. Ki-67 is a cell proliferation marker correlated with poor outcomes in many cancers. This study assessed PRAME and Ki-67 as potential prognostic markers for sentinel lymph node outcomes and survival among melanoma patients. This is a retrospective study analyzing cutaneous melanoma cases from a Brazilian cancer center (2005–2021). All cases were tested using immunohistochemistry to evaluate PRAME expression and Ki-67 index. Descriptive analysis, Spearman correlations, means comparison, Kaplan–Meier analysis, x2, and Cox models were performed. In univariate analysis of 123 cutaneous melanoma cases, high extent (P = 0.0267) and elevated intensity (P = 0.043) of PRAME were associated with decreased overall survival. The Ki-67 index was associated with overall survival (P = 0.05) and sentinel lymph node status (P = 0.0403), with a positive correlation between the markers (P = 0.0004) and between Ki-67 and Breslow thickness (P = 0.0001). However, in multivariate analysis, only Breslow thickness significantly influenced overall survival (P = 0.0003). Then, the present results can suggest that elevated PRAME and Ki-67 expression are associated with poor overall survival in cutaneous melanoma; however, in multivariate analysis, only the Breslow thickness had a significant influence. These findings highlight the potential of PRAME and Ki-67 as prognostic markers, opening frontiers that could improve strategies for treating cutaneous melanoma.
Keywords: immunohistochemistry; melanoma; neoplasm staging; pathology; skin neoplasms